ChemInform Abstract: Ca2FeMnO6: A Layered Double Perovskite with Unusual High‐Valence Fe4+ in a Layered Arrangement. Issue 33 (August 2015) - Hosaka, Yoshiteru; Ichikawa, Noriya; Saito, Takashi; Haruta, Mitsutaka; Kimoto, Koji; Kurata, Hiroki; Shimakawa, Yuichi
Abstract Brownmillerite Ca2FeMnO5 is prepared by calcination of stoichiometric amounts of CaCO3, Fe2O3, and MnCO3 (1.